Identifikasi Penggunaan Kata Baku dan Tidak Baku Pada Nama Toko di Kawasan Malioboro - Chikal Oktavindo Prasetyo; Muhammad Ardi Firmansyah Putra; Eko Wahyu Wibowo; Eva Dwi Kurniawan (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
The Malioboro area is a strategic public space in the Special Region of Yogyakarta, serving as a center for trade, tourism, and representation of local cultural identity. Shop signs in this area serve not only as business markers but also as a medium for the use of Indonesian in public spaces. However, many shop names are still written using non-standard words, outdated spellings, and variations of language that do not comply with the rules of the Big Indonesian Dictionary (KBBI) and the Enhanced Spelling System (EYD). This study aims to identify and describe the use of standard and non-standard words in shop names in the Malioboro area. The method used is descriptive qualitative with data collection techniques in the form of documentation of shop signs. The data obtained were analyzed by referring to the KBBI as a linguistic guideline and Correct Spelling System (EYD). The results of the study indicate that the use of non-standard words is still quite dominant, especially in the form of outdated spellings, the use of non-standard vocabulary, and the writing of regional names that do not comply with the rules. These deviations are generally influenced by aesthetic factors and business naming strategies. Based on these findings, it can be concluded that the use of Indonesian in public spaces, particularly on shop signs in the Malioboro area, still requires attention and guidance to comply with standard language rules and reflect the function of Indonesian as a national identity.